The adequacy of life insurance purchases - Auerbach, Alan J; Kotlikoff, Laurence J (Journal of Financial Intermediation, 1991)
This paper examines whether middle age American households purchase adequate amounts of life insurance. The analysis is based on SRI International's 1980, 1982, and 1984 surveys of the financial positions of American households. Our findings indicate that a significant minority of American wives are highly underinsured with respect to the possible deaths of their husbands. We find that 25 to 30% of wives are inadequately insured, by which we mean that they would suffer a loss in their rate of sustainable consumption of at least 30% in the event of being widowed. These findings on inadequate life insurance are even more striking if one focuses on those households in which over half of the couple's present expected value of resources is dependent on the husband's survival. The results of this paper together with those of the related literature strongly suggest that raising the share of social security benefits that are paid to surviving spouses as well as increasing employer-provided group life insurance could have a very considerable impact on the alleviation of poverty among widows, especially elderly widows.